The diagnostic utility of thoracic ultrasonography in sheep and goats with contagious caprine pleuropneumonia - Tharwat, Mohamed; Abdallah, Abdelmonem (Frontiers in Veterinary Science, 2026)
Contagious caprine pleuropneumonia (CCPP), caused by Mycoplasma capricolum subspecies capripneumoniae (Mccp), is a highly contagious respiratory disease that affects goats and, to a lesser extent, sheep. It remains a major cause of economic loss in smallholder farming systems, particularly in arid and semi-arid regions. Diagnosing CCPP in the field is challenging due to overlapping clinical signs with other respiratory diseases and limited access to confirmatory laboratory testing. Thoracic ultrasound (TUS) has emerged as a practical, non-invasive tool that enables real-time visualization of pleural effusion, lung consolidation, and fibrinous adhesions. Characteristic sonographic findings in affected goats and sheep include unilateral pleural effusion with echogenic fibrin strands, liver-like lung consolidation, and pleural septations. The utility of TUS extends beyond its established role in CCPP, offering a robust approach for the differential diagnosis of respiratory diseases in small ruminants. It facilitates timely and evidence-based clinical decision-making, supports the monitoring of therapeutic outcomes, and contributes to broader herd health management strategies. By bridging clinical and population-level applications, TUS demonstrates considerable potential as a frontline diagnostic modality to advance animal health, strengthen disease control programs, and promote sustainable rural livelihoods.